Culture-Based Psychoeducational Approach to Anti-Sexual Violence Education in Islamic Higher Education - Siti Mumun Muniroh; Miftahul Huda; Maghfur Ahmad (Khazanah Pendidikan Islam, 2024)
This article analyzes the culture-based psychoeducation approach to anti-sexual violence education, focusing on the prevention and handling of sexual violence at UIN K.H. Abdurrahman Wahid Pekalongan. This study aims to explore and critique the culture-based psychoeducation approach to strengthen the awareness, knowledge, and understanding of lecturers, students, and staff about sexual violence, and reduce cases of sexual violence. Methodologically, this study uses a case study research method. This qualitative research, the data was obtained through interviews, observations, and documentation, and analyzed through an interactive analysis model. This study involved 25 research subjects, consisting of leaders, lecturers, education staff, and students. The results of this study reveal that the culture-based psychoeducation approach, through counseling and psychological assistance, can build awareness, literacy, knowledge, and understanding of academics about sexual violence. This approach strengthens the capacity of the parties to prevent and handle cases of sexual violence on campus. An important finding of this research is that culture-based psychoeducation is an important instrument for preventing sexual violence and can create a safe, peaceful, and anti-sexual violence campus environment and culture. The theoretical contribution of this study is that culture-based psychoeducation in the context of anti-sexual violence education can reduce, prevent, and handle sexual violence. The novelty of this research is the use of cultural values in the implementation of effective psychoeducation in preventing and handling sexual violence. Practically, this study provides a model that can be adapted by similar institutions in dealing with sexual violence.